Hotspots of genetic change in Yersinia pestis - Yarong Wu; Youquan Xin; Xiaoyan Yang; Kai Song; Qingwen Zhang; Haihong Zhao; Cunxiang Li; Yong Jin; Yan Guo; Yafang Tan; Yajun Song; Huaiyu Tian; et al. (Nature Communications)
Abstract The relative contributions of mutation rate variation, selection, and recombination in shaping genomic variation in bacterial populations remain poorly understood. Here we analyze 3318 Yersinia pestis genomes, spanning nearly a century and including 2336 newly sequenced strains, to shed light on the patterns of genetic diversity and variation distribution at the population level. We identify 45 genomic regions (“hot regions”, HRs) that, although comprising a minor fraction of the genome, are hotbeds of genetic variation. These HRs are distributed non-randomly across Y. pestis phylogenetic lineages and are primarily linked to regulatory genes, underscoring their potential functional significance. We explore various factors contributing to the shaping and maintenance of HRs, including genomic context, homologous recombination, mutation rate variation and natural selection. Our findings suggest that positive selection is likely the primary driver behind the emergence of HRs, but not the sole force, as evidenced by the pronounced trend of variation purging within these regions.